Spectrum of malignancy in mixed tumors of salivary gland: A morphological and immunohistochemical review of 23 cases - Qureshi Asim; Barakzai Abrar; Ul Sahar Najam; Gulzar Rubina; Ahmad Zubair; Hassan Sheema (Wolters Kluwer Medknow Publications, 2009)
Malignancy arising in mixed tumors of the salivary gland is a distinct entity that can occur sporadically or in association with a background of pleomorphic adenoma. Carcinoma arising with a background of pleomorphic adenoma is well documented. However, there are rare occurrences of aggressive de novo carcinosarcomas of the parotid that have been reported. Various cell lineages such as the epithelial glandular cells and the stromal spindle cells are involved. We report 23 cases of tumors of the salivary gland comprising 18 cases of carcinoma ex pleomorphic adenoma, four cases of carcinosarcoma of the parotid and one case of benign metastasizing pleomorphic adenoma. The occurrence of various malignancies suggests that this phenomenon is not very uncommon and should be looked for when reporting a mixed tumor.